2017
DOI: 10.1007/s10549-017-4483-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-visualized sentinel nodes in breast cancer patients; prevalence, risk factors, and prognosis

Abstract: Patients with non-vSLNs had less favorable disease characteristics and a worse survival compared to patients with a visualized SLN. Performing an ALND was not associated with a significantly better survival in patients with non-vSLNs. However, further research on the necessity of axillary treatment in this specific patient group is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In studies conducted by Verheuvel et al and involving a group of 76 472 breast cancer patients who underwent SLNB, a failure to identify the sentinel lymph node occurred in 2.5% of performed procedures . The obtained percentage of non‐vSLN is therefore similar to the value reported by us.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In studies conducted by Verheuvel et al and involving a group of 76 472 breast cancer patients who underwent SLNB, a failure to identify the sentinel lymph node occurred in 2.5% of performed procedures . The obtained percentage of non‐vSLN is therefore similar to the value reported by us.…”
Section: Discussionsupporting
confidence: 86%
“…The obtained percentage of non‐vSLN is therefore similar to the value reported by us. The main causes increasing the percentage of SLNB failures in a statistically significant manner included a higher patient's age and a higher stage of metastatic lesions in the axillary lymph nodes ( P < .001), as well as a large size of the primary tumor ( P = .0030) . According to Dordea et al, they also include obesity, which increases a risk of fatty axillary lymph nodes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study that compared the SLNB results and patient outcome of procedures with SLN visualization and those with persistent nonvisualization after lymphoscintigraphy plus SPECT/CT or reinjection. Verheuvel et al demonstrated that SLNB procedures in which the SLN could not be identified had a worse OS (HR, 1.42; 95% CI, 1.15‐1.75) compared with those with successful SLN identification. In our study, no statistical difference in OS was found between both tumor‐negative SLNB procedure with SLN visualization and those with persistent nonvisualization (Figure ), despite having relatively more procedures with failed SLN identification, and older patients in the tumor‐negative SLNB group with persistent nonvisualization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the incidence of locoregional recurrence or DR after IBTR have reported rates ranging from 15 to 71 per cent. Voogd and colleagues reported a 5‐year DR rate of 55·8 per cent in a cohort of patients with IBTR, initially treated between 1980 and 1992.…”
Section: Discussionmentioning
confidence: 99%